Chloroplast DNA diversity associated with protected slopes and valleys for hybridizing Eucalyptus species on isolated ranges in south-eastern Australia - Pollock, L.; Bayly, M.; Nevill, Paul; Vesk, P. (2013)
Aim To relate genetic diversity to topographic features and to investigate genetic interactions between Eucalyptus species in a local centre of endemism and diversity in south-eastern Australia. Location Grampian Ranges, Victoria, Australia. Methods We documented chloroplast DNA (cpDNA) variation for a group of endemic Eucalyptus species (E. serraensis, E. verrucata and E. victoriana) that dominate rocky, high-elevation ridgelines of the Grampian Ranges and for one closely-related, widespread species (E. baxteri) occupying flanking slopes and valleys. We documented genetic patterns across the landscape using cpDNA microsatellites, and related them to topographic features (exposed west-facing versus protected east-facing slopes and valleys). We also determined the extent of local haplotype sharing between populations of endemic species and neighbouring E. baxteri downslope with cpDNA microsatellites, and haplotype sharing between the endemic group and more distantly related species (E. obliqua, E. pauciflora and E. willisii) with sequences of the JLA+ chloroplast region. Results We detected 26 cpDNA microsatellite haplotypes in a relatively small area of c.20km×50km. Populations of E. baxteri on east-facing slopes and valleys had greater cpDNA microsatellite diversity than E. baxteri and endemic species on exposed west-facing slopes. Endemic species frequently shared chloroplast haplotypes with E. baxteri downslope. Sharing of JLA+ haplotypes with species outside the endemic group was mostly restricted to E. victoriana, which had cpDNA more similar to the species from other sections of Eucalyptus (E. obliqua, E. willisii and E. pauciflora). Main conclusions Intensive sampling of related species on small isolated mountain ranges allowed us to relate genetic diversity to fine-scale habitats and to document extensive local haplotype sharing between species. This study contributes to a general understanding of the environmental conditions that enable plant population persistence by linking concentrations of genetic diversity to particular habitats.Results: We detected 26 cpDNA microsatellite haplotypes in a relatively small area of c.20km×50km. Populations of E. baxteri on east-facing slopes and valleys had greater cpDNA microsatellite diversity than E. baxteri and endemic species on exposed west-facing slopes. Endemic species frequently shared chloroplast haplotypes with E. baxteri downslope. Sharing of JLA+ haplotypes with species outside the endemic group was mostly restricted to E. victoriana, which had cpDNA more similar to the species from other sections of Eucalyptus (E. obliqua, E. willisii and E. pauciflora). Main conclusions: Intensive sampling of related species on small isolated mountain ranges allowed us to relate genetic diversity to fine-scale habitats and to document extensive local haplotype sharing between species. This study contributes to a general understanding of the environmental conditions that enable plant population persistence by linking concentrations of genetic diversity to particular habitats.